2020
DOI: 10.3389/fonc.2019.01520
|View full text |Cite
|
Sign up to set email alerts
|

Pigment Epithelium-Derived Factor Promotes the Growth and Migration of Human Esophageal Squamous Cell Carcinoma

Abstract: Pigment epithelium-derived factor (PEDF) is an oncogene found in various types of cancers. However, how PEDF affects the development of human esophageal squamous cell carcinoma (ESCC) is unknown. This study investigates the role of PEDF in ESCC cell proliferation, migration, and cell cycle both in vitro and in vivo. The PEDF expression was examined in patient tumor samples and ESCC cell lines. Short hairpin RNA technology was used to inhibit the PEDF expression in ESCC EC9706 and KYSE150 cells. In vitro cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Although PEDF has been shown to play a vital role in the metastasis of many types of tumors, there are few reports on how PEDF affects the progression of ESCC. Tang et al previously reported that PEDF could promote esophageal tumor cell proliferation and apoptosis (27). In their study, they found that PEDF is overexpressed in esophageal carcinoma tissues and cells.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although PEDF has been shown to play a vital role in the metastasis of many types of tumors, there are few reports on how PEDF affects the progression of ESCC. Tang et al previously reported that PEDF could promote esophageal tumor cell proliferation and apoptosis (27). In their study, they found that PEDF is overexpressed in esophageal carcinoma tissues and cells.…”
Section: Discussionmentioning
confidence: 83%
“…PEDF is also significantly associated with hepatocellular carcinoma progression and metastasis (26). Recently, Tang et al reported that PEDF promotes esophageal cancer cell growth (27). However, the molecular mechanism by which PEDF functions in the tumorigenesis and clinical progression of ESCC remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…For example, SERPINF1 showed anti-tumor effects by inhibiting angiogenesis in melanoma, cholangiocarcinoma, and breast cancer [ 11 , 29 , 30 ]. However, many studies substantiated that SERPINF1 promotes the growth and metastasis of esophageal cancer, liver cancer, and ovarian cancer [ 12 , 13 , 31 ]. Li et al reported that SERPINF1 exhibits contrasting intracellular and extracellular functions in hepatocellular carcinoma [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serpin family F member 1 (SERPINF1), also known as pigment epithelium-derived factor (PEDF), is a multifunctional secreted protein [ 9 ] that can exert an anti-tumor effect by inhibiting angiogenesis [ 10 , 11 ]. Interestingly, it has also been documented to promote the proliferation and invasion of tumor cells [ 12 , 13 ]. In this respect, Li et al reported that SERPINF1 exhibits contrasting intracellular and extracellular functions in hepatocellular carcinoma [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…58 LDLR, RBP4, and PEDF are known to promote tumor growth, proliferation, and migration. [59][60][61] IGF is a mitogen and is involved in regulating cell proliferation, apoptosis, and transformation by interacting with the IGF-I receptor. 62 The mitogenic effect of IGF on cancer cells is determined by bioavailability and interaction with IGF-IR, which IGFBPs regulate.…”
Section: Protein-protein Interactions and Pathways Analysismentioning
confidence: 99%